Studies on Formulation and Evaluation of Ethyl Cellulose Based Extended Release Metformin Hydrochloride Matrix Tablets - SUNDARA MOORTHY K,; SAMPATH KUMAR KP, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Monolithic matrix tablets of metformin hydrochloride were formulated as extended release tablets by employing ethyl cellulose polymer and the extended release characterization of the formulated tablets was investigated. Extended release matrix tablets containing 500 mg metformin hydrochloride were developed by changing concentration of drug : polymer (EC) in the ratio of 5:1, 5:2, 5:3 and 5:4 by direct compression. Formulations were optimized based on the acceptable tablet properties invitro and invivo drug release. The resulting formulations produced robust tablets with optimum hardness, weight variation, drug content and low friability. The result of invitro and invivo drug release studies indicated that formulation (drug:polymer =5:3), is the most successful of the study and exhibited constant and extended release of metformin hydrochloride 99-100.5% release at the end of 10 h compared with reference standard. Further, the formulation F3 was subjected to exposure at room and accelerated condition to stability studies. A decrease in release of the drug was observed on increasing polymer ratio at certain level. Before tablet compression, the resulting formulation blends were evaluated for angle of repose, bulk density, % porosity, % compressibility index and drug polymer compatibility study of drug and excipients. The t25, t50 and t90 drug release values was calculated from selected formulation F3 on every month of stability studies and comparision of both room and accelerated condition by statistical t-test, there is no difference between storage temperature. The formulation F3 was showed similar invitro and invivo drug release when compared to marketed sustained release tablet (F5M).